Variabilidade espacial do fósforo e das frações granulométricas de um Latossolo Vermelho Amarelo - Silva, Samuel de Assis; de Souza Lima, Juliao Soares; de Souza, Gustavo Soares; de Oliveira, Rone Batista; da Silva, Alessandra Fagioli [UNESP] (Univ Federal Ceara, Dept Geol, 2010)
This study was conducted to study the spatial variability of phosphorus, estimating it through cokriging taking as covariables the size fractions of soil. The study was conducted at the experimental farm INCAPER-ES. The soil was sampled in the canopy projection of culture and depth of 0-0.20 meters in an irregular mesh with 109 points. The data were initially submitted to a descriptive analysis and correlation. Through geostatistics was made the adjustment of the variograms. The P showed significant correlation with the sand and clay fractions indicating that areas with higher concentrations of clay have lower availability of this nutrient. Both fractions have equal performance as co-variable in the estimate of the levels of P in the soil.
Spatial variability of the phosphorus and granulometric fractions of a red-yellow oxisol
Keywords: Geostatistics; Soils; Match content; Oxisols; Interpolation